Perceptions towards diagnosis of prostate cancer in Tharaka Nithi County, Kenya - Kirungia, Timothy Kinoti; Kirigia, Consolata; Gitonga, Lucy; Kiruki, Silas (Universitas STRADA Indonesia, 2021)
Background: Cancers are leading cause of death in developed nations and the second leading cause of death in developing nations. One of the most frequently diagnosed cancers among men is Prostate cancer (PCa)Objective: This research study aimed at exploring the patient?s and family?s perceptions towards diagnosis of prostate cancer in Tharaka Nithi County, Kenya.Methods: The study population comprised of families and PCa patients attending Chogoria mission hospital, Magutuni sub-county hospital, Chuka county hospital and Tharaka sub-county hospital which were selected purposefully, from which a sample of 70 patients and 65 family members was obtained. Purposive sampling method was used to sample patients and families. Data were collected using interview schedules and focus group discussions and summarized using descriptive statistics. Statistical analysis for association between variables was done using chi-square tests. Results: The study revealed that; men in the age group 60-70 were most prone to the development of prostate cancer. A high percentage of patients and families perceived that prostate cancer was caused by genetic factors and should be treated by medical personnel. Over 50% of the patients and families had no idea of the symptoms of prostate cancer neither had they heard of it before the patient was diagnosed. The study also revealed that 50% of the patients suffered hypertension, 80% did not believe the diagnosis at first and over 50% perceived the diagnosis as a death sentence. PCa patients showed the highest level of acceptance and lung cancer patients the poorest acceptance of illness. Over 90% of the patients and families observed general health improvement after medication. Over 78% of the patients and family?s had embraced insurance as a way of meeting the medical expenses.Conclusion: This study demonstrated that patients and families perceived the diagnosis of prostate cancer as a death sentence. They also had low level of knowledge about PCa. A strong correlation was demonstrated between family history and increased risk of PCa. However, it was demonstrated that family history of PCa did not increase levels of knowledge on the causes of PCa.